Etanol de segunda geração no Brasil: política e translações - Lorenzi, Bruno Rossi (Universidade Federal de São Carlos, 2018)
This research aims to do a sociotechnical analyses of the research, development and production network of cellulosic ethanol from sugarcane in Brazil. To do this, we use actor-network theory to identify who are the main actors involved in these researches (companies, research and financing institutions, etc.), the overlapping policies and technologies related to the development of this product. Through this survey, carried out through bibliographical research, documentary analysis and interviews with the actors involved, we sought to identify and analyze the main translation movements of this network, such as the interests involved, disputes, negotiations, technical issues, obstacles, challenges and controversies related to the production, research and development of second generation ethanol. By mapping and reporting the initiatives and issues related to the theme, which cross both renewable energy production and Brazilian science and technology, we try to demonstrate how the E2G is still a black box open to associations and (in)definitions. With that, we hope to contribute to the current debate on energy policy and national science and technology.
Second generation ethanol in Brazil: politics and translations
Keywords: Etanol celulósico; Etanol de segunda geração; Política energética; Teoria ator-rede; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS